Implementation of Geometry Multimedia Based on Van Hiele's Thinking Theory for Enhancing Critical Thinking Ability for Grade V Students - Nurita Primasatya; Jatmiko Jatmiko (SAINTIS Publishing, 2018)
This study is a advances study of the development of geometry multimedia based on Van Hiele's thinking theory with the aim of for enhancing critical thinking ability using the ADDIE development model. In this study, a difference test was conducted to determine the effect of using geometry multimedia on students' critical thinking abilities. This experiment was conducted at SDN Mojoroto 1 and SDN Mojoroto 6 Kota Kediri. The results of the t-test analysis show that there are significant differences between the critical thinking abilities of students who use geometry multimedia based on Van Hiele's thinking theory and those who do not use geometry multimedia based on Van Hiele's Thinking Theory.